Muslim Society Response and Indonesian Clerics' Views Towards Transgender Beauty Contests: Between Belief and Reality - Tri Saputra, Rizal; Zulfikar Effendi, Luthfi; Faqihuddin, Achmad (JURNAL PENELITIAN KEISLAMAN, 2024)
This study explores the perspectives of Muslim communities in Bandung and the views of Indonesian clerics towards transgender beauty contests in Jakarta. These contests raise tensions between conservative Islamic religious values ??and modern social dynamics that are more inclusive of non-conventional gender identities. Using a qualitative approach, this study collected data through an online survey and content analysis of clerics’ sermons. The results show that the majority of Muslim respondents reject transgender beauty contests, citing their religious teachings and prevailing social norms. In addition, clerics stated that these activities violate the principle of divinity in Pancasila, emphasizing the role of religion in shaping public perceptions. This study provides insight into cultural resistance to non-conventional gender phenomena in Indonesia, as well as its implications for public policy and social understanding in a Muslim-majority context.